2016
DOI: 10.1016/j.heliyon.2016.e00163
|View full text |Cite
|
Sign up to set email alerts
|

Beyond waste: new sustainable fillers from fly ashes stabilization, obtained by low cost raw materials

Abstract: A sustainable economy can be achieved only by assessing processes finalized to optimize the use of resources. Waste can be a relevant source of energy thanks to energy-from-waste processes. Concerns regarding the toxic fly ashes can be solved by transforming them into resource as recycled materials. The commitment to recycle is driven by the need to conserve natural resources, reduce imports of raw materials, save landfill space and reduce pollution. A new method to stabilize fly ash from Municipal Solid Waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Figure 2 clearly highlights that an increase of the aging time corresponds to a decrease of pH of the solutions [32], in agreement with the already reported evidence of carbonation. This also corresponds to a decrease of the heavy metal leachability, as already observed and discussed [4,33]. In particular, concerning Pb, three months after stabilization it is sometimes lower than LOD by TXRF spectrometry, as reported in Tables 3 and 4, therefore it cannot be found in Figure 2.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Figure 2 clearly highlights that an increase of the aging time corresponds to a decrease of pH of the solutions [32], in agreement with the already reported evidence of carbonation. This also corresponds to a decrease of the heavy metal leachability, as already observed and discussed [4,33]. In particular, concerning Pb, three months after stabilization it is sometimes lower than LOD by TXRF spectrometry, as reported in Tables 3 and 4, therefore it cannot be found in Figure 2.…”
Section: Resultssupporting
confidence: 52%
“…The obtained stabilized eco-material is a powder that is very similar to the inert material obtained by using similar treatments but using other by-products (such as silica fume) instead of BA for stabilization. This allows for us to suppose that the obtained eco-materials may be used in some applications, already explored for similar products, as a substitute of natural resources [10,33,35,36]. In particular, it was shown that the obtained eco-materials are biologically safe [37][38][39], opening the interesting opportunity of the investigation of their aquatic toxicity in the next future.…”
Section: Appl Sci 2020 10 X For Peer Review 9 Of 12mentioning
confidence: 92%
See 1 more Smart Citation
“…In particular, in recent years, the idea to develop sustainable technologies for waste remediation, in the frame of Azure chemistry approach [10], has contributed to promote the use of by-products and waste materials, as stabilizing agents, instead of use natural resources [11]. For example, the COSMOS technology [12][13][14], initially based on the use of colloidal silica to stabilize leachable heavy metals (contained in FA), was improved by the replacement of commercial silica source with by-products, such as rice husk ash [15,16], silica fume [17] and sewage sludge ash [18]. Very recently, it was also shown that this kind of treatment allows us to sequestrate carbon dioxide [19], with increased sustainability of the proposed approach [20].…”
Section: Introductionmentioning
confidence: 99%
“…The use of pulp mill sludge in fired bricks develops desirable compressive strength and hence can be a potential pathway to sustainable construction [111]. The high calcium carbonate and aluminosilicate content, high fineness, spherical particle shape, and high tensile strength of PPFA makes it a suitable substitute for commercial fillers used in plastic products and polymer composites [112][113][114][115]. However, the ash from large commercial sources such as pulp and paper industries as well as wood-burning power plants needs to be preprocessed and tested to meet product specifications and industry standards for its commercialization as a plastic filler [115].…”
Section: Raw Materials For the Materials Manufacturing Industrymentioning
confidence: 99%